Use of new reactive dyes for dyeing of polyamide 6 and wool - Lišková, Vlasta; Pinto, Tiago A. D.; Burgert, Ladislav; Hrdina, Radim (Univerzita Pardubice, 2010)
This paper describes the research of newly designed and prepared reactive dyes for dyeing of polyamide 6 and wool. For this purpose, disazo reactive dyes with sulfatoethylsulfonyl group have been synthetized by the sequence of diazotation of aromatic amines and coupling reactions of formed diazonium compounds with secondary components (1-naftylaminesulfonic acids). In order to increase some colouristic properties of reactive dyes, such as fixation, exhaustion and wet fastness, the reactive group of the dyes was modified with sarcosine in several cases to form N-methyl-N-carboxymethyl-2-aminoethylsulfonyl group. In addition, dichloro-triazine dyes in modified and unmodified form have been tested as well. It was find out that the modification of reactive group with sarcosine improved significantly the colouristic properties of some reactive dyes applied to both 112 Lišková V. et al./Sci. Pap. Univ. Pardubice Ser. A 16 (2010) 111–132 investigated textile materials. Nevertheless, this method was not found to be universal for all the types of investigated reactive dyes. What can further be seen from the presented results is that among all the of investigated dyes some have been found to show especially high values of fixation that can overcome very frequent and common problems of low fixation occurring during the application of reactive dyes to dying of polyamide.
Keywords: polyamide 6; wool; reactive dyes